Effects of luseogliflozin, a sodium–glucose co‐transporter 2 inhibitor, on 24‐h glucose variability assessed by continuous glucose monitoring in Japanese patients with type 2 diabetes mellitus: a randomized, double‐blind, placebo‐controlled, crossover study. Issue 8 (4th June 2015) - Nishimura, R.; Osonoi, T.; Kanada, S.; Jinnouchi, H.; Sugio, K.; Omiya, H.; Ubukata, M.; Sakai, S.; Samukawa, Y.
<x xml:space="preserve">Abstract</x> The aim of the present study was to determine the effects of luseogliflozin on 24‐h glucose levels, assessed by continuous glucose monitoring, and on pharmacodynamic variables measured throughout the day. In this double‐blind, placebo‐controlled, crossover study, 37 patients with type 2 diabetes mellitus inadequately controlled with diet and exercise were randomized into two groups. Patients in each group first received luseogliflozin then placebo for 7 days each, or vice versa. After 7 days of treatment, the mean 24‐h glucose level was significantly lower with luseogliflozin than with placebo [mean (95% confidence interval) 145.9 (134.4–157.5) mg/dl vs 168.5 (156.9–180.0) mg/dl; p < 0.001]. The proportion of time spent with glucose levels ≥70 to ≤180 mg/dl was significantly greater with luseogliflozin than with placebo [median (interquartile range) 83.2 (67.7–96.5)% vs 71.9 (46.9–83.3)%; p < 0.001] without inducing hypoglycaemia. The decrease in glucose levels was accompanied by reductions in serum insulin levels throughout the day.